Pengaruh Investment Opportunity Set, Dividend Payout Ratio, dan Sales Growth Terhadap firm Value Pada Sub Sektor Makanan dan Minuman Yang Terdaftar di Bei Tahun 2020-2024 - Fanny Febriani; Asnahwati (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the influence of Investment Opportunity Set (IOS), Dividend Payout Ratio, and Sales Growth on Firm Value for companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The research employs a quantitative approach using multiple linear regression. The research sample was selected using a purposive sampling method, and the data used were the companies' annual financial reports. The hypothesis testing results show that, individually, the three independent variables have no significant effect on Firm Value. The partial test (t- test) proved that IOS has no significant influence on firm value. Similarly, the Dividend Payout Ratio and Sales Growth were also not found to have a significant effect. Furthermore, the simultaneous test (F-test) confirmed that, collectively, these three variables also do not have a significant influence on Firm Value. The low Adjusted R-squared value indicates that only a small portion of the variation in firm value can be explained by this model, while the remaining 92.1% is explained by other variables outside the model. This study's conclusion rejects the initial hypotheses and suggests that other factors play a more dominant role in determining firm value within this subsector.